2001
DOI: 10.2466/pms.2001.92.3.786
|View full text |Cite
|
Sign up to set email alerts
|

Central and Peripheral Visual Reaction Time of Soccer Players and Nonathletes

Abstract: Visual Reaction Time (RT) was measured by presenting three different sizes of stimulus to the central and peripheral fields of vision in 6 soccer players and 6 nonathletes. An electromyogram was recorded from the flexor digitorum superficialis muscle of the responding forearm. Peripheral visual RT was longer in comparison to central visual RT due to an increment in Premotor Time. The soccer players showed shorter Premotor Times during central and peripheral visual RT tasks than nonathletes, suggesting that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
61
1
13

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 21 publications
(16 reference statements)
10
61
1
13
Order By: Relevance
“…Our results partially indicate a shorter reaction time (p < 0.01) in athletes compared with nonathletes, albeit only in the groups of footballers and volleyball players. This confirms earlier reports by Ando et al (2001) who determined changes in the bioelectrical charge in the forearm muscles to assess the reaction to stimuli appearing in the central and peripheral vision in highly-skilled footballers. The specificity of football requires a state of readiness to respond to stimuli that may arise in the field of view.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results partially indicate a shorter reaction time (p < 0.01) in athletes compared with nonathletes, albeit only in the groups of footballers and volleyball players. This confirms earlier reports by Ando et al (2001) who determined changes in the bioelectrical charge in the forearm muscles to assess the reaction to stimuli appearing in the central and peripheral vision in highly-skilled footballers. The specificity of football requires a state of readiness to respond to stimuli that may arise in the field of view.…”
Section: Discussionsupporting
confidence: 91%
“…For example, Baylor and Spirduso (1988) found that regular physical activity improves the efficiency of simple reaction times, more with regards to the pre-motor fraction (70%) than to motor fraction of the reaction time (30%). Many researchers confirm this thesis, reporting faster response times in athletes in comparison with non-athletes (Ando, Kida, Oda, 2001;Kioumourtzoglou, Kourtessis, Michalopoulou, Derri, 1998;Kokubu, Ando, Kida, Oda, 2006;Overney, Blanke, Herzog, 2008;Piras, Lobietti, Squatrito, 2014;Vansteenkiste, Vaeyens, Zeuwts, Philippaerts, Lenoir, 2014;Zwierko, Osiński, Lubiński, Czepita, Florkiewicz, 2010). On the other hand, not all articles confirm the existence of a relationship between the efficiency of motor reactions and physical fitness (Cojocarlu and Abalasel …”
Section: Introductionmentioning
confidence: 95%
“…The younger group, however, had better results in tests investigating static visual acuity, contrast sensitivity, and stereoscopic examination (hardware skills). Ando et al (2001) also proved that the central and peripheral visual reaction time of soccer players is significantly shorter than that of nonathletes. Their results suggest that soccer players are better able to respond quickly to a stimulus presented to both their peripheral and central visual fields.…”
Section: Discussionmentioning
confidence: 78%
“…Visual acuity at the extreme periphery falls to 4 percent (Williams et al, 1999), which is why peripheral visual reaction time is significantly longer than central reaction time. The study by Ando et al (2001) indicates that peripheral visual reaction time is slower than central visual reaction time due to an increment in premotor time. It seems that a higher level of visual perception in athletes is more related to recognition speed and responsiveness to stimuli than the functioning of the visual system in the peripheral field.…”
Section: Discussionmentioning
confidence: 98%
“…recentes estudos têm demonstrado que atletas possuem um processamento central mais eficiente que não-atletas, provenientes de possíveis facilitações neurais concedidas pela prática esportiva (1,16,20) . Com a prática, o atleta aprende a identificar quais são os estímulos mais adequados e a probabilidade dos mesmos ocorrerem para a tomada de decisão de determinadas respostas motoras (10) .…”
Section: Introductionunclassified